Organizational and cognitive aspects of forming communicative competence technology of headmasters in Ukraine and developed countries - Chebotarova, I. O. (Problems of Engineer-Pedagogical Education, 2018)
The present work highlights organizational and cognitive aspects of forming communicative competence technology of headmasters in the process of their professional training. As part of the study we proved and analysed the specific features of technological aspects of forming the communicative competence of the headmasters in national education system and advanced countries (USA, Germany, United Kingdom). Having analyzed the world and national experience in creation of communicative competence, we made the conclusion that the urgent need of communicative competence of headmasters only started to be realized. All of this is a result in the fact that the management students have to gain the communicative skills mostly by “natural” way – out of the higher educational institution. While in the developed countries the communicative competence formation is the key factor of the efficient learning. Forming of the communicative skills takes place simultaneously with gaining of professional knowledge and is based on cognitive and oratorical principles.